Glen Doyle's material arts cross-training for figure skaters - Lisa, T. (2001)
The martial arts, specifically Kung fu, is an excellent cross-training vehicle for the sport of figure skating. Using Elvis Stojko as the "filter", Glen's cross-training program was developed and refined. It is a hybrid of Kung fu based moves and general exercises designed to enhance the physical as well as the mental skills necessary to be successful in the sport of figure skating. All of the exercises and techniques that make up the cross-training program have been tested and are used by Elvis.